Akibat Hukum Kepailitan Terhadap Kreditor Pemegang Hak Tanggungan dalam Eksekusi Hak Tanggungan - Titie Syahnaz Natalia (Program Studi Magister Manajemen FE Unsri, 2018)
Tujuan-The purpose of this study was to how did the legal consequences of bankruptcy to creditors as holders of guaranty rights in executing guaranty rights of debitors. This was a descriptive and normative business law research.Metode-Data were collected from primary, secondary, and tertiary business law materials. Data were analyzed and discussed to draw conclusions qualitatively to answer the research problems.Results-showed that the causes why separate creditors had exclusive authorities upon bankruptcy was that to provide legal security upon guaranty to return credits had been granted to debtors, because without legal security on the credits, there would be no institutions (both individual or legal entity) willing to provide credits to debtors. Creditor rights as holders of guaranty rights were in form of parate eksekusi and execution based on execution power to the Certificate of Guaranty rights which was limited by Act of bankruptcy.Originality-Keywords: separate creditors, guaranty right, bankruptcy